EFFECT OF PLANT GROWTH REGULATORS FOR INDUCTION OF PARTHENOCARPIC FRUIT IN KAKROL (Momordica dioica Roxb.) - Chowdhury, R. N.; Rasul, M. G.; Islam, A. K. M. Aminul; Mian, M. A. K.; Ahmed, J. U. (Bangladesh Journal of Plant Breeding and Genetics, 2007)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->An experiment was conducted to find out the suitable plant growth regulator(s) for inducing parthenocarpic fruit in kakrol (Momordica dioicia Roxb). Four plant growth regulators, viz. NAA and 2, 4-D (Auxins), Fulmet (Cytokinine) and GA3 (Gibberellic acid) were sprayed at three stages (a day before anthesis, at anthesis, a day after anthesis). Out of four growth regulators 2, 4-D and fulmet induced parthenocarpic fruit development. Fruit set percent, final fruit weight, fruit length and fruit diameter varied significantly with different treatment combinations. 2, 4-D at 50 ppm when applied at anthesis showed better performance in inducing parthenocarpy. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17030